Repurchasing Shares on a Second Trading Line - Chung, Dennis Y.; Isakov, Dušan; Pérignon, Christophe (Review of Finance, 2007)
Abstract This paper studies a unique buyback method allowing firms to reacquire their own shares on a separate trading line where only the firm is allowed to buy shares. This share repurchase method is called the Second Trading Line and has been extensively used by Swiss companies since 1997. This type of repurchase is unique for two reasons. First, unlike open market programs, the repurchasing company does not trade anonymously. Second, all transactions made by the repurchasing firm are publicly available in real time to every market participant. This is a case of instantaneous disclosure which contrasts sharply with other markets characterized by delayed or no disclosure. We document that the daily repurchase decision is statistically associated with short-term price changes and the release of firm-specific news. We also find that repurchases on the second trading line have a beneficial impact on the liquidity of repurchasing firms. Exchanges and regulators may consider the second trading line an attractive share reacquisition mechanism because of its transparency and positive liquidity effects.